The Methodological Provisions of Financial Regulation of the Development of the Processing Fruit and Vegetable Industry - Pasichnyk Yurii V.; Lomako Evgeniya P.; Strikhovskyi Dmytro M. (Bìznes Inform, 2022)
The article is aimed at identifying the peculiarities of the functioning of the processing fruit and vegetable industry in the postmodern era and the formation of methodological provisions for its further development. To form these provisions, scientific approaches are used, which include: substantiation of the theoretical basis of methodological provisions; analysis of industrial production during 2003-2020, as well as exports and imports of processed fruit and vegetable products; assessment of potential opportunities for these products; development of a structural scheme of these provisions. According to the analysis of the total production volumes of processed fruit and vegetable products and the dynamics of export-import operations of these products for 2019-2020 significant disparities are identified and it is indicated that their dynamics are unstable, with significant fluctuations, which confirms the general trends in the functioning of the processing fruit and vegetable industry. Particularly unfavorable tendencies are manifested in the increase in imports of individual canned vegetables, juices, fruits, berries, jam, marmalade. Attention is focused on the fact that it is not possible to maintain a positive tendency towards a permanent increase in export supplies of canned tomatoes without vinegar and juices of fruits and berries. A significant result of the research is the development of a structural scheme of methodological provisions of the financial regulation of the development of the processing fruit and vegetable industry, taking into account the identified characteristics of the postmodern era; potential opportunities for producers of agricultural products and processing enterprises; coordination of efforts of the relevant ministry, territorial communities and other organizations. According to the results of the research, it is concluded that it is advisable to increase funding from the State Budget of Ukraine of this industry sector and continue scientific researches for the formation of methodological provisions and the development of recommendations for financing schemes in favor of this industry.